The Existence of Village Regulations as a Realization of Good Governance in Development Implementation (Study in Putatgede Village, Ngampel District, Kendal Regency) - Ulfia Pamujiningsih (Indonesian State Law Review, 2019)
The concepts and theories used in this study are the concept of good governance, Stufenbau theory, development model theory, and economic theory based on Pancasila. The research approach is qualitative law with a type of juridical-sociological research. village development. Data sources use primary, secondary, and tertiary data sources with data collection techniques in the form of interviews, documentation, and observation. The records are then checked for validity through data validity with triangulation techniques and using data analysis with qualitative analysis. Putatgede Village Administration has promulgated eleven Decree for 2016 with details of five of them in the field of development. Putatgede Village development priority is used for infrastructure development because the majority of the village community with a total of 719 (per head of family) is a food crop farming family. The results showed the existence of Village Regulations in the field of development implementation can realize good governance which includes the principles of legal certainty, orderly governance, public order, openness, proportionality, professionalism, accountability, effectiveness and efficiency, local wisdom, diversity, and participatory. The Putatgede Village development model based on village regulations is Pancasila-based economic development with a sustainable development approach. The conclusions of this study are (1) indicators of good governance through the implementation of Article 24 of Law Number 6 of 2014 concerning Villages that have been implemented well; (2) The model of community economic development is implemented by placing the village community as the subject and object of development. Suggestions for this research are (1) the recommended training on good governance for the Village Government; (2) the need for additional economic activities in Putatgede Village, especially the development of micro, small and medium enterprises.